THE GLYCEMIC INDEX ON THE SPORT DRINKS AS FACTOR OF MAINTENANCE OF GLYCEMIA: A NEW PARADIGM (Fiep Bulletin - online, 2014)
The carbohydrate drinks ingestion during the exercise improves the performance due to maintenance of the glycemia in the normal levels, saving the muscular and hepatic glycogen. According to this, the present study aimed to compare the effect of the carbohydrate drinks ingestion of different glycemic index in the maintenance of the glycemia in a military group in only an exercise session. Thirty eight Lifeguards of Rio de Janeiro were instructed to run along the beach for 60 minutes, each group having 200 ml of a specific carbohydrated drink every 15 minutes. Straight after the test, the glycemia was checked. The tested drinks that simultaneously present carbohydrates of high and low glycemic index were Carbo Plus®, Gatorade®, Açaí Guaraviton diluted by 50%®, Orange Juice diluted by 50% and Coconut Water; the drink that presents exclusively carbohydrate of high glycemic index is the Homemade Serum. All the tested drinks, apart from the Homemade Serum, showed themselves able to keep the glycemia in the normal levels. What differed them from the Homemade Serum was the glycemic index of their carbohydrates: They had high glycemic index carbohydrate (glucose, sugar) and low glycemia index (fructose, maltodextrin) in their composition, which are digested and absorbed slowly, while the Homemade Serum presented only sugar, which high glycemic index raises the insulinemia abruptedly and provides reactive hipoglycemia.
Keywords: Glycemic index; sport drinks; glycemia